DEVELOPMENT OF POP-UP BOOK-BASED PICTURE MEDIA TO IMPROVE THE ABILITY OF WRITING INDONESIAN LANGUAGE NARRATIVES IN GRADE IV - Aulia, Usna; Rambe, Andina Halimsyah (International Journal of Cultural and Social Science, 2025)
This study aims to evaluate the validity, practicality, and effectiveness of Pop-Up Book-based image series media in enhancing narrative writing skills in Indonesian language lessons for fourth-grade students at MIS Al-Washliyah Timbang Lawan. Using a Research and Development (R&D) approach with the ADDIE model, the research includes stages of Analysis, Design, Development, Implementation, and Evaluation. The product underwent validation by media, material, and language experts. Results showed that media experts rated the Pop-Up Book learning media at 95.7% (very valid), material experts at 72.3% (valid), and language experts at 94.2% (very valid). In terms of practicality, educators gave it a 96% rating (very practical), while students rated it 93.1% (very practical). The writing ability observation sheet showed that students’ writing skills improved significantly, from 65.6% to 95% after using the media. In conclusion, the Pop-Up Book-based learning media is effective in improving students' writing skills.